A Sociolinguistic Of Register Used By Photograper In Social Media - Agusta, Asri Kartika, Drs . H. Maryadi, MA, Dra. Siti Zuhriah Ar., M.Hum (2013)
The research is proposed to analyze about the sociolinguistic analysis of register used in photographer in social media (fotografer.net). In this photography portal website is used different language that used by people in daily conversation. There are specific term to explain the event that happens in fotografer.net. Many English register in fotografer.net. In this case, this research analyzes : 1. What are the linguistic forms of the register used in photographer conversation?. 2.What are the meaning of the register used in photographer conversation?. 3.What are the motives of the register used in photographer conversation?.Based on the analyzes the researcher finds the data based 1.the linguistics form (7 data of noun, 2 data of adjective, 1 data of verb, 1 data of compound, 2 data of clipping, 9 data of abbreviation, 1 data of noun phrase and 1 data of verb phrase). 2. the meaning, the writer find finds 10 data in lexical meaning and 20 data in contextual meaning. 3 The motive the writer finds 21 data of need filling motive and 9 data of need filling motive.